The slaying of Meghanada a Ramayana from colonial Bengal - Dutt, Michael Madhusudan, 1824-1873.; Seely, Clinton B.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2004)
Datte's deft intermingling of western and eastern literary traditions brought about a sea change in South Asian literature. His masterpiece is now accessible to readers of English in this translation, complete with introduction, notes and a glossary.
Translated from Bengali.
Description based on print version record.
Includes bibliographical references and index.
Keywords: x; Electronic books